2008
DOI: 10.1002/jbm.a.32213
|View full text |Cite
|
Sign up to set email alerts
|

Macroporous hydroxyapatite scaffolds for bone tissue engineering applications: Physicochemical characterization and assessment of rat bone marrow stromal cell viability

Abstract: In this work, a new methodology is reported for developing hydroxyapatite (HA) scaffolds using an organic sacrifice template. The novelty of work consists of possibility of obtaining porous and highly interconnected scaffolds mimicking the sacrificial component. Our purpose consisted of evaluating the physicochemical properties of the HA scaffolds by means of Fourier transform infra-red spectroscopy, X-ray diffraction analysis, and scanning electron microscopy (SEM) attached with an X-ray detector. The HA scaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 49 publications
1
63
0
1
Order By: Relevance
“…Oliveira et al 21) reported that the relatively high bioactivity of HA is related to a phenomenon involving the dissolution of calcium phosphate ions from HA. Weng et al 22) and Radin and Ducheyne 23) reported that dissolution of calcium and phosphate ions from the outermost surface of HA implants leads to an increase in the local concentrations of these ions that favors biological apatite precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al 21) reported that the relatively high bioactivity of HA is related to a phenomenon involving the dissolution of calcium phosphate ions from HA. Weng et al 22) and Radin and Ducheyne 23) reported that dissolution of calcium and phosphate ions from the outermost surface of HA implants leads to an increase in the local concentrations of these ions that favors biological apatite precipitation.…”
Section: Discussionmentioning
confidence: 99%
“…The following chemicals were used as obtained for the preparation of the bioceramic material; bentonite clay-(OH) 4 …”
Section: Methodsmentioning
confidence: 99%
“…Bentonite clay of the type (OH) 4 Si 8 Al 4 O 20 ·nH 2 O shown in Figure 2(a) was reacted in strong basic medium to initially afford sodium metasilicate (reaction equation is shown elsewhere [26]) after evaporating the alkaline filtrate slowly to dryness at 120˚C. The waterglass obtained, Figure 2(b), from this reaction is hydrolysed under acidic conditions to silicic acid which undergoes condensation to disilicic acid and further reaction to a polycondensed hydrogel [26,27].…”
Section: Composition Of the Porous Btc-derived Bioglass Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveira et al [8] developed hydroxyapatite (HA) single scaffolds with a porosity of~70 % and macropore diameter in the range of 50-600 μm with high pore uniformity and interconnectivity across the scaffolds by means of sponge replica method (Fig. 1).…”
Section: Scaffoldsmentioning
confidence: 99%